If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(23 + -1x + -2y) + 2(23 + -1x + -7) = 20 (23 * 2 + -1x * 2 + -2y * 2) + 2(23 + -1x + -7) = 20 (46 + -2x + -4y) + 2(23 + -1x + -7) = 20 Reorder the terms: 46 + -2x + -4y + 2(23 + -7 + -1x) = 20 Combine like terms: 23 + -7 = 16 46 + -2x + -4y + 2(16 + -1x) = 20 46 + -2x + -4y + (16 * 2 + -1x * 2) = 20 46 + -2x + -4y + (32 + -2x) = 20 Reorder the terms: 46 + 32 + -2x + -2x + -4y = 20 Combine like terms: 46 + 32 = 78 78 + -2x + -2x + -4y = 20 Combine like terms: -2x + -2x = -4x 78 + -4x + -4y = 20 Solving 78 + -4x + -4y = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-78' to each side of the equation. 78 + -4x + -78 + -4y = 20 + -78 Reorder the terms: 78 + -78 + -4x + -4y = 20 + -78 Combine like terms: 78 + -78 = 0 0 + -4x + -4y = 20 + -78 -4x + -4y = 20 + -78 Combine like terms: 20 + -78 = -58 -4x + -4y = -58 Add '4y' to each side of the equation. -4x + -4y + 4y = -58 + 4y Combine like terms: -4y + 4y = 0 -4x + 0 = -58 + 4y -4x = -58 + 4y Divide each side by '-4'. x = 14.5 + -1y Simplifying x = 14.5 + -1y
| 4(x+3)=3x+3 | | 2(x+2)=3x-4 | | 2v+4=-2(2v+4) | | -6-7(5k-7)=3k-11(1+4k) | | 0=2x^3+8x+1 | | y=392-47.5x | | (-2*-2*-2*-2)-3(6+7)= | | 10=2x+8x | | 2+5r=26 | | 3n+24= | | x+y+2z=23 | | -1+x=x+11 | | x+6=1+2x+8 | | 0.16(y-8)+0.10y=0.18y-0.09(10) | | 11(-7n+4)=-23-11n | | 1.5k+3.5=-4 | | -3x-24=-6x+33 | | 10(1-p)=10(p+9) | | 12u+17y=891 | | 36b-9=18b+3 | | 27-2x=x | | 5+2r=26 | | (3x+2y)2= | | 13xsquared+26x+14=0 | | -12+10x=9x+13 | | -22(x+1)=-11(x+2) | | 9-2g=-5 | | 36b-1=18b+3 | | 2.5x+3.5=-3.5 | | 4t^2-17t=15 | | -12(x-2)=4(x+6) | | 3x-(2x+7)=4x+2 |